2015
DOI: 10.4236/abb.2015.612075
|View full text |Cite
|
Sign up to set email alerts
|

Metal Salts Assisted Enzyme-Based Extraction of Stevioside from the Leaves of <i>Stevia rebaudiana</i> Bertoni

Abstract: Stevioside, extracted from the leaves of Stevia rebaudiana Bertoni, is a natural, high intensity, lowcaloric sweetener with wide therapeutic activities. Conventional stevioside extraction methodologies involve the use of non-green solvents, supercritical fluids, microwaves, etc., however, all these processes are expensive, time-consuming and eco-unfriendly. Therefore an alternative process is desired for the isolation of stevioside. In this study, a novel enzyme-mediated extraction (EME) method has been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Water extraction Abou et al, 2010;Inamake et al, 2010;Rao et al, 2012;Afandi et al, 2013;Deshmukh and Kedari, 2014;Gonzalez et al, 2014 Methanol extraction Liu et al, 1997;Pol et al, 2007;Deshmukh andKedari, 2014 Ethanol extraction Erkucuk et al, 2009;Deshmukh and Kedari, 2014 Pressurized fluid extraction (PFE) Pol et al, 2007 Microwave-assisted extraction (MAE) Jataik et al, 2009;Teo et al, 2009;Javad et al, 2014 Ultrasonic-assisted Extraction (UAE) Zlabur et al, 2015 Pressurized hot water extraction(PHWE) Teo et al, 2009;Tiwari et al, 2014 Supercritical fluid extraction (SFE) Pasquel et al, 2000;Choi et al, 2002;Yoda et al, 2003;Pol et al, 2007;Erkucuk et al, 2009Enzymatic extraction Puri et al, 2012Rao et al, 2015 Kolb et al, 2001;Woelwer et al, 2010;Hoekstra et al, 2009;Kumari et al, 2016HPLC C18 Vanek et al, 2001Abou et al, 2010;Afandi et al, 2013;Gonzalez et al, 2015;Gonzalez et al, 2014;Kubica et al, 2015;Samah et al, 2013;Javad et al, (Woelwer, 2012).…”
Section: Extraction Methods Reference(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Water extraction Abou et al, 2010;Inamake et al, 2010;Rao et al, 2012;Afandi et al, 2013;Deshmukh and Kedari, 2014;Gonzalez et al, 2014 Methanol extraction Liu et al, 1997;Pol et al, 2007;Deshmukh andKedari, 2014 Ethanol extraction Erkucuk et al, 2009;Deshmukh and Kedari, 2014 Pressurized fluid extraction (PFE) Pol et al, 2007 Microwave-assisted extraction (MAE) Jataik et al, 2009;Teo et al, 2009;Javad et al, 2014 Ultrasonic-assisted Extraction (UAE) Zlabur et al, 2015 Pressurized hot water extraction(PHWE) Teo et al, 2009;Tiwari et al, 2014 Supercritical fluid extraction (SFE) Pasquel et al, 2000;Choi et al, 2002;Yoda et al, 2003;Pol et al, 2007;Erkucuk et al, 2009Enzymatic extraction Puri et al, 2012Rao et al, 2015 Kolb et al, 2001;Woelwer et al, 2010;Hoekstra et al, 2009;Kumari et al, 2016HPLC C18 Vanek et al, 2001Abou et al, 2010;Afandi et al, 2013;Gonzalez et al, 2015;Gonzalez et al, 2014;Kubica et al, 2015;Samah et al, 2013;Javad et al, (Woelwer, 2012).…”
Section: Extraction Methods Reference(s)mentioning
confidence: 99%
“…While, patent has claimed that CO 2 could be used as a solvent and methanol, ethanol and acetone as a cosolvant for steviol glycosides extraction (Kienle, 1990). Extractions of sweet glycosides using various enzymes have been also used successfully (Puri et al, 2012;Rao et al, 2015). Puri et al (2012) revealed a novel enzyme-mediated extraction (EME) method for stevioside extraction from leaves of S. rebaudiana.…”
Section: Major Sweet Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al. (2015) used hydrolytic enzymes aided by transition metal salts (FeCl 3 ) to pretreat dry stevia leaves, followed by PHWE to release stevioside. Cellulase pretreated with metal salt enhanced the yield of stevioside to about 72%, with 98% purity.…”
Section: Extraction Techniques Of Rebaudioside a From Stevia Leavesmentioning
confidence: 99%
“…Enzyme-mediated extraction EME, a "green" method, is a practical alternative approach for recovering valuable compounds from stevia leaves (Rao et al, 2015). In this process, enzymes can help break down the plant's cell wall, thereby facilitating the recovery of target compounds in the cell.…”
Section: 6mentioning
confidence: 99%